Sedimentary Characteristics and Developmental Models of the Cambrian Dolostone-Evaporite Paragenesis System in the Sichuan Basin. (24th September 2022) - Wang, Jixuan; Hu, Zhonggui; Li, Shilin; Tong, Zebin; Guo, Yanbo; Pang, Yulai; Zhu, Yixin; Cai, Quansheng
Abstract : The Cambrian strata of Sichuan Basin, China, present many dolomite-evaporite paragenesis systems (DEPS), which contain oil and gas resources for industrial exploitation. However, despite their wide distribution, the formation models and influencing factors of DEPS remain poorly understood. By analyzing an abundance of literature from China, this study comprehensively summarizes the sedimentary characteristics, combination patterns of rocks, and formation models of DEPS. The research significance, research questions, and future research directions of DEPS are also clarified. Firstly, the distribution of DEPS is clarified based on published studies: DEPS are widely distributed in the Longwangmiao Formation, the Gaotai Formation, and the Xixiangchi Formation of the eastern and southern Sichuan Basin. Evaporite and dolostone combination patterns in DEPS include the following modes: interbedding of dolostone and evaporite, evaporite overlying thick dolostone, thick dolostone mixed with thin evaporite, and thick evaporite mixed with thin dolostone. Secondly, five types of evaporites and five types of dolostones have been identified. Thirdly, spatiotemporal distribution, influencing factors, and developmental models are summarized. Studies on DEPS provide new insight into the origin of dolomite. Such research also provides theoretical guidance for the exploration of oil and gas resources in DEPS.